Artificial Intelligence Application Encounter and Ethical Literacy Among Nigerian Postgraduate Students: An Empirical Investigation - Simeon Ayoade Adedokun; Dorcas Atinuke Adedokun (Southeast Asian Journal of Global Trends and Issues in Education, 2026)
Background: Nigerian universities have accelerated AI deployment across teaching, assessment, and administration, yet functional ethical literacy among postgraduate students remains low. Objective: This study investigated whether direct, hands-on encounters with AI applications predict higher ethical awareness and stronger prioritization of ethical concerns among postgraduate students at Ladoke Akintola University of Technology (LAUTECH), Ogbomoso, Nigeria. Method: A quantitative survey design was adopted. Data were collected from 200 postgraduate students classified into those with AI encounter (n = 124, 62.0%) and those without (n = 76, 38.0%). Independent Samples t-tests were applied at a 0.05 significance level. Results: Students with AI encounter demonstrated significantly higher ethical awareness scores (M = 3.90 vs. M = 3.20; t(198) = 4.23, p < 0.01; d = 1.12) and higher ethical prioritization scores (M = 4.15 vs. M = 3.50; t(198) = 3.18, p < 0.05; d = 0.92). Both effect sizes are large by Cohen’s conventions. Conclusion: AI encounter is a strong predictor of ethical literacy. Contribution: The findings provide empirical justification for integrating experiential AI ethics modules into postgraduate curricula in Nigerian higher education.